Rethinking causality and inequality in students' degree outcomes. Issue 3 (3rd April 2023) - Sabri, Duna
Abstract: Inequality in students' degree outcomes has been a concern for the higher education sector and the UK government for more than a decade. Since its inception in 2018, the Office for Students in England has prioritised the need for evidence of causality through requiring institutions to evaluate the effectiveness of their initiatives as set out in Access and Participation Plans. This policy development responds to several reports which identify a dearth of evidence-based interventions and scant knowledge of 'what works'. This paper traces the interplay between policy and research, focusing on the assumptions they make about causality. It concludes that unwarranted positions are taken in both spheres of practice, making progress unlikely. A conception of causality situated in extant formal theory on evidential pluralism and that draws on current practices would help us address inequality more effectively. Alternative framings of the problem of inequality in students' degree outcomes is offered.